2009 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition 2009
DOI: 10.1109/date.2009.5090778
|View full text |Cite
|
Sign up to set email alerts
|

Multi-domain clock skew scheduling-aware register placement to optimize clock distribution network

Abstract: Abstract. Multi-domain clock skew scheduling is a cost effective technique for performance improvement. However, the required wire length and area overhead due to phase shifters for realizing such clock scheduler may be considerable if registers are placed without considering assigned skews. Focusing on this issue, in this paper, we propose a skew scheduling-aware register placement algorithm that enables clock tree optimization by considering domains assigned to registers in placement. Our experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…It is observed that our register relocation achieves a significant cost reduction in both BST and RT clock network structures, which is up to 50 percents in clock wire length, much more than [8]. However, the increase on total wire length is NOT negligible in the trade-off, and so the dynamic power estimation on each circuit is shown in Fig.3.…”
Section: Methodsmentioning
confidence: 88%
See 4 more Smart Citations
“…It is observed that our register relocation achieves a significant cost reduction in both BST and RT clock network structures, which is up to 50 percents in clock wire length, much more than [8]. However, the increase on total wire length is NOT negligible in the trade-off, and so the dynamic power estimation on each circuit is shown in Fig.3.…”
Section: Methodsmentioning
confidence: 88%
“…Second, since the partitioning results of all the cells including registers might be refined, the amount of affected cells might be large and their displacements might be huge to have different timing in data paths, where the assumption for clock skew scheduling was violated. Therefore, after register location refinement, either setup or hold constraints in some timing paths might be violated, which is the major drawback in [8].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations